Effectiveness and safety of inspiratory muscle training in patients with pulmonary hypertension: A systematic review and meta-analysis - Luo, Zeruxin; Qian, Hong; Zhang, Xiu; Wang, Yuqiang; Wang, Jing; Yu, Pengming (Frontiers in Cardiovascular Medicine, 2022)
Background Inspiratory muscle training (IMT) is a simple and well-tolerated physical therapy that increases respiratory muscle strength and relieving the degree of dyspnea and fatigue. Therefore, it may be used as a transitional modality before exercise training or as a specific physical therapy intervention for those who are diagnosed with respiratory muscle weakness. However, the current evidence on IMT in pulmonary hypertension (PH) patients is inconclusive. The purpose of this systematic review and meta-analysis was to summarize the current role of IMT in this group of patients. Methods PubMed, EMBASE, and Cochrane databases were searched through May 2022. Trials examining the feasibility and effectiveness of IMT in PH patients. Outcome measures included adverse events, training adherence and compliance, maximum inspiratory pressure (MIP), maximum expiratory pressure (MEP), forced vital capacity (FVC%), forced expiratory volume in 1 s (FEV1%), FEV1/FVC%, 6 min walk distance (6MWD), Peak VO2, dyspnea, and fatigue perception after the IMT training program. Only randomized controlled trials were included. The Cochrane Risk of Bias tool for controlled trials was adopted to assess study quality. Statistical heterogeneity was evaluated with the chi-square test and I2 statistic. Mean differences and 95% confidence intervals (CIs) were estimated. Results We ultimately identified four studies that met the criteria. These studies comprised 80 patients with 16 males and 64 females. The mean age was 53.25. The main types of PH were group I (pulmonary arterial hypertension, 95%) and group IV (chronic thromboembolic PH, 5%). No severe adverse events were reported in the included studies. IMT had a significant effect on improving MIP (18.89 cmH2O; 95% CI: 9.43–28.35, P < 0.001) and MEP (8.06 cmH2O; 95% CI: 2.39–13.73; P = 0.005), increase in the 6MWD (30.16 m; 95% CI: 1.53–58.79; P = 0.04). No significant improvement was found in pulmonary function (P > 0.05), and uncertain effect on the quality of life (QoL) score. Conclusion Based on currently limited evidence, IMT is an effective physical therapy for increasing respiratory muscle function and exercise capacity, but still a lack of evidence on dyspnea and fatigue levels, pulmonary function, and QoL in PH patients. There are reasons to believe that IMT is a promising intervention in PH patients, enriching rehabilitation options and serving as a bridge before formal exercise training. It is expected that IMT will play an important role in the future clinical pathway of physical therapy for this group of patients. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO/logout.php], identifier [CRD42022335972].